Animo Mahasiswa Terhadap Program Kreativitas Mahasiswa Paradigma N-Act Mcclelland di Universitas Muhammadiyah Makassar - Fasikul Ikhsan; Sam’un Mukramin (Universitas Katolik Widya Karya Malang, 2023)
Providing motivation is something that is absolutely necessary for world campuses to increase learning motivation and learning outcomes. Internal and external motivation is a requirement that cannot be ignored. This study aims to analyze the causes of the increase in N-Act members of the University of Muhammadiyah Makassar through PKM. The research method uses qualitative methods with descriptive analysis research types. The data was obtained through interviews with 5 students from Muhammadiyah Makassar University. Analysis of presentation of motivation is based on David McClelland's theory. The research results: 1) Achievement of N-Ach Through Student Creativity Programs, 2) Giving motivation encourages the desire to achieve, 3) The influence of providing information encourages students to achieve achievements. The implication of providing motivation is not only to increase interest in developing student creativity but also to create an atmosphere of competitive competition within the scope of the University of Muhammadiyah Makassar